Peer feedback: moving from assessment of learning to assessment for learning - Sigrun M Wagner (Association for Learning Development in Higher Education (ALDinHE), 2016)
The following case study showcases a model of academic peer learning that has demonstrated clear links to learning development in final year students. The paper discusses the introduction of a new assessment structure for a 15 credit course unit usually taken by 90 students in the form of a short discursive essay (500 words) due early in the first teaching term. This essay is peer assessed in groups of four students. The peer feedback and tutor mark then serve as formative feedback (feed forward) for the main, longer essay (2-2,500 words) due in the second teaching term. Following the outline of the case background, details of the peer assessment are provided, including its development and structure. The new assessment structure has resulted in deeper learning, positive student feedback, fewer student complaints with regard to grades received for the main essay, and better preparation for the final exam. Reflections are offered in the conclusion.